2015
DOI: 10.1038/cddis.2015.264
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stress response is critical for gemcitabine resistance in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with marked chemoresistance and a 5-year survival rate of 7%. The integrated stress response (ISR) is a cytoprotective pathway initiated in response to exposure to various environmental stimuli. We used pancreatic cancer cells (PCCs) that are highly resistant to gemcitabine (Gem) and an orthotopic mouse model to investigate the role of the ISR in Gem chemoresistance. Gem induced eIF2 phosphorylation and downstream transcription factors ATF4 and CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 63 publications
3
82
1
Order By: Relevance
“…In contrast to the direction explored here, replication stress can also induce the ISR, as has been reported in the case of the nucleoside analogue gemcitabine (49). Of note, however, gemcitabine was found to induce eIF2alpha phosphorylation with a delay of at least 6 hours.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to the direction explored here, replication stress can also induce the ISR, as has been reported in the case of the nucleoside analogue gemcitabine (49). Of note, however, gemcitabine was found to induce eIF2alpha phosphorylation with a delay of at least 6 hours.…”
Section: Discussioncontrasting
confidence: 55%
“…ISRIB reverses stress‐induced mRNA translation repression and inhibits stress granule formation, enhancing stress‐induced apoptosis as a result of a defective stress response in tumour cells . Preclinical studies using a pancreatic ductal adenocarcinoma model showed promising anti‐tumour activity for ISRIB .…”
Section: Targeting the Translational Machinery In Cancermentioning
confidence: 99%
“…One mechanism for cancer cells to combat chemotherapy is to use a protective stress response (Jaramillo and Zhang 2013;Sui et al 2013;Palam et al 2015). The validated SMYD2 targets (i.e., RB, p53, HSP90, PARP1, PTEN, HSP90, and MAPKAPK3) are involved at some level in stress signaling, which led us to postulate that activation of SMYD2 might represent one mechanism regulating the response of PDAC cells to chemotherapy.…”
Section: Smyd2 Inhibition Enhances the Effects Of Chemotherapy In Pdacmentioning
confidence: 99%